The influence of active hamstring stiffness on markers of isotonic muscle performance - Langan, S. P.; Murphy, T.; Johnson, W. M.; Carreker, J. D.; Riemann, B. L. (Sports, 2021)
Background: Previous research demonstrates hamstring muscle-tendon stiffness (HMTS) influences isometric strength, landing biomechanics and architectural tissue properties. However, the influence on kinetics & kinematics during other modes of strength testing (isotonic dynamometry) has yet to be established. Purpose: Investigate how HMTS influences kinetics and kinematics during a novel isotonic muscle performance test which has never been done for the hamstrings. Previous work using dynamometry has been limited to isometric or isokinetic contractions, so the novelty arises from our custom isotonic protocol which allows quantitative assessment of the stretch-shortening cycle. Methods: Twenty-six recreationally active individuals (15 males, 11 females, 23.8 ± 2.5 years) completed baseline testing for anthropometry and maximum isometric hamstring strength (MVIC). At least 48 h later, subjects completed a measure of HMTS (damped oscillation technique) followed by an isotonic knee flexion test (eccentric velocity 180°/s; concentric torque 25% of MVIC). Separate linear regression models with examination of residuals were conducted between HMTS and each muscle performance variable. Standardized coefficients determined the magnitude of the relationships. Results: Significance was found for all outcome variables tested. HMTS and rate of torque development demonstrated the strongest relationship followed by isotonic concentric peak torque. The weakest relationship observed was with isometric peak torque. Conclusions: These findings build off previous work quantifying HMTS by showing HMTS more strongly relates to dynamic versus static muscle testing and identifies the potential clinical utility of isotonic dynamometry.